TiO Supported on Quartz Wool for Photocatalytic Oxidation of Hydrogen Sulphide - Magdalena Grześkowiak; Rafał J. Wróbel; Dariusz Moszyński; Sylwia Mozia; Joanna Grzechulska-Damszel; Antoni W. Morawski; Jacek Przepiórski (Adsorption Science & Technology)
A spacial system consisting of TiO 2 on a fibrous support was prepared by hydrolysis of titanium isopropoxide in the presence of quartz wool, followed by calcination. The material was characterized by X-ray diffraction, nitrogen adsorption–desorption at 77 K, X-ray photoelectron spectroscopy, scanning electron microscopy and energy-dispersive X-ray spectroscopy. The TiO 2 /support system was examined as a photocatalyst for UV-assisted oxidation of H 2 S in air. The results obtained confirmed a superior performance of the TiO 2 /support system over TiO 2 powder. H 2 S underwent oxidation to elemental sulphur and/or S 6+ . The relative amounts of these species were influenced by humidity.